IMPLIKASI PUSAT PERTUMBUHAN DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DAN PENERIMAAN DI KABUPATEN MUARA ENIM - Pamela Galina (Jurnal Ekonomi Pembangunan, 2012)
This research was aimed at identifying the influence of (1) investment on economic growth, and (2) economic growth on revenues of Muara Enim Country. The secondary data consisted of those collected from Central Statistics Bureau, Bank  of Indonesia, Investment Board, other agencies; they dealt with the data on investments, regional revenues, gross regional domestic products, and economic growth by district in the country. The research results show that the investment elasticity on the economic growth pointed at 0.58%. In case the investment changed into 1%, this means that the elasticity increased by 0.58%. The elasticity of the economic growth to revenues was -0.21%. In other words, if the economic growth increased by 1%, the revenues decreased by -0.21%. Districts of Semende Darat Laut, Lawang Kidul, Muara Enim, Talang Ubi and Gelumbang were identified as the areas that experienced the economic growth. To enable each district to make significant economic growth, generate incomes for the citizens, more jobs. The Country Government is recommended to implement strategic plans. The strategies include the development of human resources quality, and efficient policies on investments, trade, infrastructure building, agencies. These policies should be managed in an integrated way in order to ensure overall regional development and social welfare of the citizens. Keywords: Growth Centre, Investment, Economic Growth, Revenues